Improved Energy Consumption and Resource Utilization through Sensor Virtualization in Smart home (International Journal of Engineering and Computer Science, 2015)
Wireless sensor networks have tremendous importance in our daily life style. Recently in the fields of WSN, the concept Virtualization of wireless sensor network i.e. VSN is a new promising research approach. The state of the art technology can provide the opportunity to build an economic business model for application area such as smart home, health care, because of the involved infrastructure cost. In this paper we propose an agent based approach of sensor virtualization concept in Smart home by efficiently utilizing the available resources for multiple Smart home applications through scheduling sensing activity and reduce Energy Consumption. We have implemented and evaluated the sensor virtualization scheme in real time environment. The evaluation method shows that the virtualization of s ensor network technology reduces the overall cost and complexity